Fictional names: a critical study of some theories not committed to the existence of fictional entities - Napolano, Angelo (2013)
Fictional names such as Sherlock Holmes, Tom Sawyer or Superman originate in fiction. We also employ them in ordinary conversations. However, when we ask what these terms refer to and what speakers think when they employ them, a host of problems arise. Whilst an anti-realist perspective will assimilate them to the broader category of empty-names; a realistic perspective, articulable in different ways, argues for the existence of fictional entities as their referents. Each stance faces puzzles which are difficult to resolve. Generally speaking, if we think or talk about something when we use fictional names, what is it we are thinking or talking about? How do referential relations work in this context? If, on the other hand, we speak about nothing when we use a fictional name, how do we understand the linguistic processes which go on and which give us the impression of speaking about something? I will provide an overview of both theoretical stances and the different problems they face; however, my focus will be on the anti-realistic perspective. Specifically, I will discuss two main ways of treating the supposed emptiness of fictional names: I will argue against the employment of the notion of ‘gappy propositions’ and in favour of Gareth Evans’ and Kendall Walton’s idea that speakers’ utterances which appear to make reference to fictional entities can be understood as acts of pretence of a certain sort. I will in particular discuss the many objections to David Braun’s anti-realist proposal. I will consider the weaknesses of the pragmatic account built by Fred Adams, Gary Fuller and Robert Stecker around the key notion of ‘gappy propositions’. Finally, I will present Kendall Walton’s view and answer the objection of implausibility which is often aimed at it, providing an understanding of acts of pretence in terms of acts of communication.